Microinstability and Internal Impingement of the Shoulder - Mistry, Alpesh; Campbell, Rob S.D. (Seminars in Musculoskeletal Radiology, 2015)
Internal impingement refers to entrapment of the rotator cuff and capsulolabral structures between the glenoid and humeral head in certain positions of the shoulder. This may be a normal physiologic phenomenon. However, it may occur as a pathologic process, especially in sports with repetitive overhead activity. The two types of internal impingement are posterosuperior and anterosuperior, with established radiologic manifestations. These conditions were initially thought to be due to repetitive mechanical entrapment. Subsequent observational studies have led to the concepts of microinstability and glenohumeral internal rotatory deficit. Controversy remains regarding the exact pathophysiology, reflected in the variable outcomes in the treatment of these syndromes. The reporting radiologist must be aware of the constellation of image findings to alert the referring physician to the possibility of microinstability and internal impingement.
Keywords: microinstability; internal impingement; shoulder; glenohumeral internal rotation deficit